Health indicators and costs among outpatients according to physical activity level and obesity - Morais, Luana C. [UNESP]; Rocha, Ana Paula R.; Turi-Lynch, Bruna C. [UNESP]; Ferro, Izabela S. [UNESP]; Koyama, Kelly A.K.; Araújo, Monique Y.C.; Codogno, Jamile S. (Elsevier, 2019)
Objective: How biochemical variables influence the costs of the Brazilian National Healthcare System, according to body composition and physical activity. Methods: Participated in this study 168 patients. Biochemical variables were glucose, triglycerides, total cholesterol, high, low, very low density lipoprotein and C-reactive protein (CRP). For the cost analysis the medical records was analyzed. Physical activity was assessed through questionnaire. Body adiposity was assessed by body mass index. Four groups were defined according body adiposity and physical activity. Results: The active obese group had higher values of very low density lipoprotein and triglycerides when compared to the inactive obese. The non-obese inactive group had lower values of non-high density lipoprotein compared to the inactive obese. The non-obese active group presented lower insulin value when compared to the inactive obese. The inactive obese group presented higher values in the CRP when compared to the non-obese active and inactive groups when compared to non-obese and active obese group. There was a positive correlation between insulin, glucose, CRP and drug and total costs. Conclusions: Biochemical variables were different according to body composition and physical activity. Insulin, glucose and CRP were related to cost in drugs and total costs.
Keywords: National healthcare system; Obesity; Physical activity